Pengembangan Media Ajar Papan Target Terhadap Ketepatan Smash Bola Voli - Siahaan, Alex Mandri; Ginting, Ramadan (Jurnal Tematik, 2026)
This study aims to produce and test the Target Board Teaching Media on Volleyball Smash Skills in Class XI Students of Methodist High School Lubuk Pakam. The method used in this study is the research and development (R&D) method from Borg and Gall which includes 10 general steps. The research design used is pre-test post-test control group design. The subjects of this study were Class XI Students of Methodist High School Lubuk Pakam. The Volleyball Smash Skills Teaching Media Model for Class XI Students of Methodist High School Lubuk Pakam in 2025 is the Target Board. The instruments used for this model consist of interviews and questionnaires, while the instrument for measuring volleyball skills is the target board. The results of the study show that: (1) The Target Board Teaching Media Model on Volleyball Smash Skills in Class XI Students of Methodist High School Lubuk Pakam, (2) the effectiveness test of the Target Board Teaching Media Model on Volleyball Smash Skills in Class XI Students of Methodist High School Lubuk Pakam shows a significant influence. The results of the N-gain test The experimental group's score obtained a Mean value = 58.4816 or equal to 58% included in the effective category. Meanwhile, the results of the N-gain test The control group's score obtained a Mean value = 24.7949 or equal to 24% included in the less effective category. So it can be stated that the Target Board Teaching Media training model is effective given to class XI students.